A167 CATEGORIZING ENDOSCOPIC SEVERITY OF CROHN'S DISEASE USING THE MODIFIED MULTIPLIER SES-CD (MM-SES-CD). (21st February 2022) - Pray, C; Narula, N; Wong, E C; Colombel, J; Marshall, J; Daperno, M; Reinisch, W; Dulai, P S
Abstract: Background: The modified multiplier of the Simple Endoscopic Score for Crohn's Disease (MM-SES-CD) is a novel internally validated endoscopic scoring tool that quantifies the endoscopic burden of Crohn's Disease (CD). The MM-SES-CD considers the same endoscopic parameters and anatomical locations of the commonly used SES-CD, but acknowledges the different prognostic value of each parameter by assigning an individual weight to each category based on its impact on probability of achieving ER. Previous published work has demonstrated the MM-SES-CD can predict one-year endoscopic remission. This analysis aims to establish thresholds of the MM-SES-CD to classify CD endoscopic burden into very mild or inactive disease, mild, moderate, and severe disease based on the probability of achieving ER on active therapy at one-year. Aims: The purpose of this analysis was to assess for numerical cut-offs of baseline MM-SES-CD to distinguish between mild, moderate and severe endoscopic CD activity based on the likelihood of one year ER. Additionally, the relationship between baseline MM-SES-CD score and likelihood of one-year CR (CDAI <150) was evaluated. Methods: This post-hoc analysis included pooled data from three CD clinical trials including the UNITI studies, the EXTEND study, and a biosimilar infliximab study, referred to as 'CT-P13 study' (n=350 patients, baseline SES-CD ≥3 with confirmed ulceration). Maximum Youden Index calculations were used to determine thresholds for severity. Chi-square tests of trend were used to compare achievement of ER between severity categories, and Kaplan-Meier survival curve analysis was used to compare time to clinical remission (CR). Results: MM-SES-CD severity categories were established as very mild or in remission (score <14), mild (score ≥14 to <31), moderate (≥31 to <45), and severe (score ≥45), which were predictive of one-year ER (50%, 30.3%, 21.7%, 8.8% respectively p<0.001). Lower MM-SES-CD scores had numerically higher rates of one-year CR, and time to CR over 52 weeks was superior to those with higher scores (p=0.0492). Conclusions: We have established numerical cut-offs of the MM-SES-CD that categorize endoscopic disease severity and are prognostic for one-year ER and CR. Achievement of one-year outcomes stratified by baseline MM-SES-CD Funding Agencies: None